Analysis of Voltage Source Inverter with Photovoltaic Renewable Energy Source for Improving Power Quality in Solar - Shabbeer Basha, K. Hazee; Raj, S. Solomon; Sivakumar, S.; Padmarasan, M.; Laxmaiah, G.; Raj, K. Bharath (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Power quality analysis are based on converter technique and grid connected linear, nonlinear loads. Power quality Contains different issues: stability, reliability, and THD (Total harmonic distortion). In the existing Perturb and Observe (P&O) algorithm technique and Cascaded Multilevel Inverter (DC-AC) methods have low distortion and power losses. So, to overcome problems the Power point maximum tracking based Incremental Conductance (IC) algorithm and Voltage Source Inverter (VSI) are to improve the energy generated by the cause of voltage distribution. The input source is a photovoltaic (PV) power generating unit of fundamental power generation calculated based on irradiance temperature. MPPT tracks the input voltage and produces maximum power output within particular conservation environments. The IC algorithm controls the MPPT output for proper pulse width modulation and regulates the interlope control. The DC–DC converter operates both bucks and boost for given proper conversion technique in inverter and output load. A voltage Source Inverter (VSI) converts DC to AC, which operates the switching operation based on pulse width modulation; the switching operation of the duty cycle continues to move in the opposite direction from that of the interruption when the whole system is at the right opposite end of the Power point maximum tracking for the positive structure working directions. The output result gains better maximum output voltage, reduces harmonics distortion and improve power quality.